The Economic Effects of Democratic Participation - Dennis C. Mueller; Thomas Stratmann (Center for Economic Studies and ifo Institute (CESifo), 2002)
Considerable concern has been expressed in recent years about declines in voter participation rates in the United States and in several other major democratic countries. Some feel low participation rates introduce a class bias into the political process and thereby worsen the outcomes from it. Little empirical work exists, however, that measures the effects of lower participation on the welfare of a country. This paper begins to fill this void. It presents cross-national evidence that high levels of democratic participation are associated with more equal distributions of income. The paper's results also imply, however, that this reduction in income inequality comes at a cost. High participation rates are related to larger government sectors which in turn lead to slower economic growth. We also present evidence of the capture of government by upper income groups in Latin and Central American countries.
Keywords: 330